South Pole Lake ApRES Radar - Hills, Benjamin (U.S. Antarctic Program (USAP) Data Center, 2021)
These are ground-based radar data collected from a subglacial lake ~15 km from the geographic South Pole. Data were collected with the Autonomous phase-sensitive Radio Echo Sounder (ApRES) (Nicholls et al., 2015). The intention of this dataset is to be used for vertical velocity structure and interpretation.